Survival benefit of TACE combined with sorafenib for hepatocellular carcinoma patients with portal vein tumor thrombus - Luo, Bin; Chen, Zhen-Hua; Zhang, Xiu-Ping; Wang, Meng; Cheng, Shu-Qun (Translational Cancer Research, 2017)
Hepatocellular carcinoma (HCC) is the most common primary hepatic malignant tumor and the world’s fifth most common tumor. Portal vein tumor thrombosis (PVTT) have been appeared about 10–40% for HCC patients (1,2). PVTT predicted a dismal prognosis, because they promoted HCC recurrence and metastasis, impaired hepatic reserves, raised portal vein pressure, and reduced portal vein flow. The median survival time (MST) of HCC and PVTT patients is obviously decreased compared to those without PVTT. According to the invading location in portal vein of the PVTT, the studies from our group proposed “Cheng’s classification” to divided the PVTT into four types (type I, being segmental/sectoral branches of portal vein; type II, being left and/or right portal vein; type III, being main portal vein trunk, and type IV, being superior mesenteric vein) (3,4). According to the guidelines from Barcelona Clinic Liver Cancer (BCLC), HCC with PVTT was classified as advanced HCC (BCLC stage C). They recommended sorafenib as the standard treatments for patients with advanced HCC. However, some studies have shown that some treatment modalities like transarterial chemoembolization (TACE), radiotherapy (RT), transarterial radioembolization (TARE), and resection-based multimodal treatments in some selected HCC and PVTT patients may prefer better outcomes than sorafenib (5-7). Our comments were responded to “editorial on combination treatment beyond sorafenib alone for HCC with portal vein tumor thrombosis”, and indicated that the new advances treatments were applied for HCC patients with PVTT.